Blended Learning Model using Kahoot Application on Students' Learning Outcomes - Evi Sulistiani Susiana; Tsamarul Hizbi; F Fartina (Center for Intellectual Property and Technology Innovation, Universitas Sains Al-Qur'an, 2025)
This research aims to determine the effect of abstract the Kahoot-assisted blended learning model on student learning outcomes in class X global warming material at SMK Qurrota A'yun NWDI Joben for the 2024/2025 academic year. This type of research uses a quantitative approach, preexperimental research methods with a one-group pretest-posttest design. The population in this study was one class, namely class x with a total of 26 students. The sample in this study was all students in one class. One class was given pretest as control values class, then given treatment and then given posttest as experimental values class. The results of data analysis show that the average score of student learning outcomes on the pretest is 54.23 and the average score of learning outcomes on the posttest value is 86.04. The data analysis technique uses the t test with the results of data analysis obtaining a t count of 16.61 and a t table value of 2.01 with a significance level of 5% and dk = 50. These results show that tcount > ttable (16.61 > 2.01) which means that Ho is rejected and Ha is accepted. It can be said that there is an influence of the Kahoot-assisted blended learning model on student learning outcomes for class x global warming material at SMK Qurrota A'yun NWDI Joben